Library Automation: The Gateway to an AI-Driven Revolution - Nadim Akhtar; Farhana Saeed Hashmi; Muhammad Nadeem Akhtar; Dr. Fauz Dar Khan; Sidra Batool; Rehana Kousar (Dialogue Social Science Review (DSSR), 2025)
In this digital era, every discipline of life has adopted new trends related to technology and the mood of work. In this scenario, libraries adopted the latest technology to serve the public with fastest & accurate services. To serve this purpose, libraries started automation in the university libraries of Lahore, Pakistan. The main objective of this study to investigate & to know about the current status of automation in libraries and assess whether automation can increase the utilization of library resources and services in a developing country like Pakistan. Quantitative research based on survey method was used in this research. The study was conducted in the context of university libraries because automation process started in universities some thirty years ago. Accordingly, respondents were university library professionals who were involved in automation activities at any level. The study found that even more than three decades have been passed, but the automation landscape of the university libraries is still not mature. Libraries are still struggling towards achieving the fully automated status to expand their services in its full potential. Professionals skills level on automated systems is also at infancy stage. The findings of the study portray a clear canvas for the stakeholders to devise policies for improving the infrastructure of the educational institutions to compete with the challenging situations. Also, for the academicians to formulate such curriculum which enhance the skills of professionals in the age of artificial intelligence.